Synthesis and Characterization of Molybdenum Nitride (Mo2N) Nanopowders - Sidana, Harneet Kaur (My University, 2017)
Transition metal nitrides have gained an escalation in the recent years due to their remarkable physical and chemical properties. They have high melting point and form refractory compounds. They also possess high hardness, high wear resistance and superconductive properties. Nowadays they are also being used as catalysts. Among these nitrides, Mo2N is being extensively studied, due to its distinguishable features. Mo2N finds a wide industrial applications and catalytic activities. Taking this into account, β-Mo2N nanopowders have been synthesized in this present study via a simple reduction-nitridation technique, using ammonium heptamolybdate tetrahydrate (AHM) (NH4)6Mo7O24.4H2O as molybdenum source, sodium azide (NaN3) as nitrogen source with magnesium (Mg) as reducing agent. Various trials were performed to obtain pure phase β-Mo2N with the variation of holding time, reaction temperature and precursor quantity. The samples were synthesized in a stainless steel (high-grade) autoclave in a pot furnace. Characterizations were done using XRD, FE-SEM and HR-TEM. It was observed that pure phase β-Mo2N was formed when precursor AHM was varied at a duration of 12 hrs while the temperature was kept at 700 oC which was confirmed by XRD pattern. FE-SEM results showed that the as synthesized samples possess platelet morphology, which was further confirmed by HRTEM. Various factors which influences the synthesis of β-Mo2N has been discussed in the present work.
Keywords: Molybdenum nitride; in-situ synthesis; nanopowder; Williamson-Hall analysis